MANAJEMEN KURIKULUM BERWAWASAN LINGKUNGAN DI SEKOLAH ALAM PACITAN KABUPATEN PACITAN TAHUN PELAJARAN 2016/2017 - Haryanti, Haryanti (El-Hayah, 2018)
Abstract:This study was conducted with the aim; (1) to know the management of environmentally sound curriculum in Pacitan natural elementary school; (2) to know about environmentally sound curriculum implemented in SD Alam Pacitan, (3) to know the obstacle factor and support the implementation of environmentally sound management in SD Alam Pacitan; (4) to know the solution in overcoming the problem of implementation of environment-friendly curriculum management in SD Alam Pacitan Lesson 2016/2017.           This research includes descriptive qualitative research type. The setting of the research is done at Sekolah Alam Pacitan in the even semester. Lesson Year 2016/2017 Subject of Principal and Teacher Research. Informant, School Committee, Student. The research instrument is the researcher. Methods of data collection using observation methods involved, in-depth interviews, and documentation. Examination of data validity by extension of data analysis using data collection of researcher in field, deep observation and triangulation. Data analysis techniques by describing the process of tracking and arranging systematically transcripts interviews, field notes and other materials.            The results showed that: (1) The management of environmentally sound curriculum at Sekolah Alam Pacitan is divided into 3 phases: planning includes designing RPP and syllabus of education unit level curriculum (KTSP) on each subject, implementation includes educator to apply environmental issue and inculcate responsibility environment. Using lecture, discussion and question and answer methods; (2) Selected learning techniques adapted to the characteristics of students and materials; (3) Environmental-oriented learning in each subject by utilizing the school environment has been well done can be seen as a teaching material in the practice and create innovative works related to the environment such as compost, dodol pace, juice pace.Keywords: Environmental Based Curriculum